The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0102-05362013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento de tubérculos de três cultivares de batata sob condições de estiagem

Abstract: Tuber yield of tree potato cultivars under drought conditionsThe performance of the potato cultivars BRS Ana, BRS Clara, and Agata was verified, grown under naturally-induced water stress, in relation to tuber yield. The experiment was carried out in the 2011/2012 season, in the Anta Gorda locality, Canoinhas, Santa Catarina state, Brazil. The experimental design was randomized complete blocks with eight replications, and plots with three rows of 10 plants in each row. One hundred twelve days after planting, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
4
0
5
Order By: Relevance
“…Cultivar BRS Clara was the most tolerant as none disease symptoms were recorded until the last evaluation. These results sustain Pereira et al (2013) whose records for late blight concluded that BRS Clara possess foliar resistance against late blight. On the other hand, cultivar Agata showed a high susceptibility to late blight, as a high AUDPC record was recorded on this cultivar: at the 55 DAP, plants of cultivar Agata showed no effective photosynthetic leaf area due to severe disease incidence.…”
Section: Summer Field Cultivationsupporting
confidence: 82%
See 1 more Smart Citation
“…Cultivar BRS Clara was the most tolerant as none disease symptoms were recorded until the last evaluation. These results sustain Pereira et al (2013) whose records for late blight concluded that BRS Clara possess foliar resistance against late blight. On the other hand, cultivar Agata showed a high susceptibility to late blight, as a high AUDPC record was recorded on this cultivar: at the 55 DAP, plants of cultivar Agata showed no effective photosynthetic leaf area due to severe disease incidence.…”
Section: Summer Field Cultivationsupporting
confidence: 82%
“…The other cultivars showed similar results, with an average of 9.0 tubers per plant. Silva et al (2013) observed similar tuber number for cultivars BRS Ana and BRS Clara: 8.37 and 10.7 per plant, respectively; but a higher total tuber number for cultivar Agata (13.9 tubers/plant) in a experiment under conventional cultivation system, using synthetic fertilizers and agrochemical pest management.…”
Section: Summer Field Cultivationmentioning
confidence: 65%
“…The cultivar of potato most planted by the producers is cv. Agate, which is characterized by desirable characteristics due to early tuberization, good tuber appearance and productivity (PINELI, 2006;SILVA, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…O fotoperíodo é longo e a pressão de seleção para fatores bióticos e abióticos que afetam a cultura lá é baixa, diferente do Brasil, resultando em cultivares que, quando plantados em condições subtropicais e tropicais, apresentam períodos vegetativos (Rodrigues, 2006) e produtividades menores. Para conseguir maior produtividade é necessário o uso intensivo de fertilizantes, o que pode levar a menor sustentabilidade da cultura (Silva et al, 2013). Desta forma, a obtenção de cultivares adaptados às condições de cultivo nas diversas regiões produtoras brasileiras e com resistência às principais doenças é a alternativa viável para tornar a cultura produtiva e rentável ao agricultor (Gadum et al, 2003).…”
Section: Introductionunclassified
“…Presume-se que cultivares desenvolvidos para condições de solos ácidos, como ocorre no Brasil, apresentem raízes mais profundas, sendo mais tolerantes à seca (Silva et al, 2013) e mais eficientes no aproveitamento dos nutrientes do solo.…”
Section: Introductionunclassified